CARCASS CHARACTERISTICS, ORGAN PROPORTION, HAEMATOLOGY, SERUM CHEMISTRY AND DIGESTIBILITY OF BROILER CHICKENS FED UMUCASS 36 CASSAVA ROOT MEAL - Adedokun, Olubukola O. (FUDMA JOURNAL OF SCIENCES, 2023)
A week old 150 Arbor Acre strain of broilers fed UMUCASS 36 cassava root meal were used to evaluate the carcass characteristics, organ proportion, blood and serum chemistry and digestibility of the birds. The cassava was harvested, washed, peeled, chipped, oven dried and milled. The processed cassava root meal was used to formulate five diets, at 0, 25, 50, 75 and 100% levels designated D1, D2, D3, D4 and D5 respectively to replace maize. The birds were assigned in a Completely Randomized Design to five treatments with three replicates of ten birds per replicate. The carcass characteristics of broilers fed diet D2 was more superior and significantly (P>0.05) different from other broilers on the other diets.  The superiority reflected in the bled weight, plucked weight, dressed weight and dressing percentage with the following values: 2136.67g, 2056.67g, 1723.33g and 77.71% respectively. The same trend was seen the values of the cut parts. Broilers on diet D5 had the highest percentage weight in heart (0.81%), liver (3.81%), gizzard (3.31%) and kidney (1.29%) while broilers on diet D2 had the least percentage of heart weight (0.38%), liver (1.33%), gizzard (1.11%) and kidney (0.57%). The experimental diets had no deleterious effects on the haematology and the blood serum of the broilers. Broilers placed on diet D2 had the best digestibility coefficients in all the digestibility parameters when compared with broiler chickens fed other diets. From the ongoing, it can be concluded that broilers on diet D2 performed best therefore, diet D2 is recommended.
Keywords: umucass 36; broiler chickens; blood; carcass; digestibility